Property Management of Chinese Chan Buddhist Monasteries: Strengthening Sustainable Trajectory of Religious Establishments - Xie, Honghai; Beliatte, Metteyya (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
This paper undertakes a comprehensive examination of property management paradigms within the precincts of Chinese Buddhist monasteries, further elucidating individual monks' asset management practices. Drawing from historiographical and documentary resources, this research contextualizes the multifaceted evolution of monastic property ownership, acquisition, and stewardship throughout successive epochs. This analysis illuminates that such paradigms have been sculpted by an intricate confluence of factors, encompassing: dynastic decrees, socio-economic fluxes, ecclesiastical ordinances, and symbiotic interactions with the laity. We discern distinct stratagems of property management, oscillating between the collective stewardship emblematic of cohesive monastic communities and the individual asset holdings of mendicants. In the contemporary milieu, with the accelerative thrust of urbanization and China's mutable regulatory milieu, monastic conglomerates grapple with intricate juxtapositions of canonical religious tenets, exigent economic imperatives, and state apparatuses. This manifests in innovative modus operandi such as lay-partnerships, entrepreneurial ventures, and more. This scholarly endeavor augments the extant literature on ecclesiastical asset management, proffering pivotal insights into the syncretic interplay between religious confraternities and their ambient socio-economic matrices. Furthermore, discerning these intricate practices and their foundational philosophies could catalyze efficacious policy formulations, aligning with cultural conservation objectives and ensuring the sustainable trajectory of religious establishments while contributing to broader global goals such as the Sustainable Development Goals (SDGs), particularly in promoting sustainable communities, cultural preservation, and responsible resource management.